Keterkaiatan antara Citra Merek, Kepercayaan Merek, dan Celebrity Endorser Terhadap Keputusan Pembelian dan Peran Minat Beli Sebagai Mediator - Natha Prawira, Anak Agung Ngurah Dicky; Suardana, Raka (Universitas Batanghari Jambi, 2024)
The fashion industry in Indonesia has undergone major changes with the development of the athleisure trend, which combines elements of sports with everyday fashion. Puma, as one of the leading brands, faces challenges in expanding its market share amidst increasingly fierce competition. This study aims to examine the impact of Citra Merek, Kepercayaan Merek, and celebrity endorsement on Puma consumers' purchasing decisions, and to evaluate the role of purchase intention as a mediating variable. A quantitative approach was used in this study, with data analysis through SEM-PLS 4.. The results showed that Citra Merek, which emphasizes modern and trendy aspects, has a significant positive effect on purchase intention and purchase decision. Kepercayaan Merek was also proven to have a positive effect on both variables. In addition, celebrities who become endorsers with high reputations also increase purchase intention and purchase decision. Purchase intention plays an important role as a mediator in the relationship between Citra Merek, Kepercayaan Merek, and celebrities with purchase decision. This study provides further insight into the interaction of marketing factors and highlights the importance of exploring further into other factors that influence purchase decisions.